Aspects of the development of the comprehensive information security system in the information systems - Nosyk, Andrii Mihajlovych; Kucherenko, Yurii; Nosyk, Kateryna Andriivna (Харківський національний університет радіоелектроніки, 2020)
Here are considered some aspects on the comprehensive information security system development of any information system of civil purposes, which manages the critical infrastructure or process in a relevant field, or control systems for special purposes. The basis for the functioning of these systems is information, and because of it the issue of protection is paramount in their functioning. The questions on the choice of general security policy in them, the choice of methods for identification and authentication, authentication of documents, circulating them. This will conceptually define the future of information security records they elaborate.
Keywords: information; information systems; comprehensive information security system; method; unauthorized access; security policy